Thinking crisis/thinking nation. An aproach to Mariategui's political problematics - Berríos Cavieres, Claudio (2023)
This work addresses the problems of nation, modernity and tradition in the thought of José Carlos Mariátegui. The period of political and cultural crisis in those years allowed him to configure new proposals around the approach to Peruvian history and its close relationship with a comprehensive and comprehensive national project.